IMPROVING STUDENTSâ€™ READING COMPREHENSION OF BUSINESS TEXT BY USING â€œTELLSâ€ STRATEGY AT FIRST YEAR STUDENTS OF STATE POLYTECHNIC OF BENGKALIS - Aswandi Aswandi (INOVISH JOURNAL, 2019)
Reading comprehension of business texts is necessary for students. However, many students, especially D3- Business Administration department of state polytechnic of Bengkalis faced dificulties in comprehending the business texts. Therefore, TELLS Strategy was proposed. TELLS strategy is a strategy which stands for Study the title; Examine for clues; Look for Important words; Look for hard words, and identify the setting. This article aimed at finding out to what extent the strategy to improve the students reading comprehension of business text and the factors that influence the changes. This classroom action research was conducted in two cycles. The result found that the students’ score in reading comprehension of business texts test increased. The average score of students in cycle 1 was 64 and in cycle 2 was 70. Then, the factors that influence the improvement of students’ reading comprehension of business texts were interesting teaching material, teacher’s role, and students’ willingness to do all procedures of the strategy. In conclusion, the implementation of TELLS strategy could improve the students’ reading comprehension of business texts majoring Business Administration improved both students’ score in reading tests and their interest in reading activities.